2017
DOI: 10.1186/s40798-017-0111-2
|View full text |Cite|
|
Sign up to set email alerts
|

Aerobic but not Resistance Exercise Can Induce Inflammatory Pathways via Toll-Like 2 and 4: a Systematic Review

Abstract: BackgroundOnly a few studies have addressed the relationship between toll-like receptors 2 and 4 (TLR2 and TLR4) and the production of local and systemic cytokines in response to physical exercise, and they have produced conflicting results. We aimed to determine whether acute and chronic exercise outcomes are associated with changes in TLR2 and TLR4 expression and signaling and if so, the mechanisms that connect them.MethodsPubMed database were consulted. This systematic review selected 39 articles, 26 involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 177 publications
(286 reference statements)
2
32
0
2
Order By: Relevance
“…TLR2 is another member of the TLRs family that is also involved in the cell response to immune stimuli, and shares with TLR4 its downstream signalling cascade. A recent systematic review showed that chronic exercise has anti-inflammatory effects on the organism through the downregulation of both TLR2 and TLR4 at the protein and gene expression levels [ 56 ], which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…TLR2 is another member of the TLRs family that is also involved in the cell response to immune stimuli, and shares with TLR4 its downstream signalling cascade. A recent systematic review showed that chronic exercise has anti-inflammatory effects on the organism through the downregulation of both TLR2 and TLR4 at the protein and gene expression levels [ 56 ], which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of physical exercise on TLR expression and on inflammatory cytokines production have been demonstrated in few studies, till now it is still an area of controversy. Furthermore, the effect of acute exercise on TLR expression has received even less attention (Cavalcante et al 2018). Early studies state that prolonged strenuous exercise causes suppression of both TLR expression and function.…”
Section: Physical Exercisementioning
confidence: 99%
“…The released cytokines promote inflammatory responses, affect the physiological processes of the host body, and represent as the master contributors of many diseases (Bresnahan and Tanumihardjo 2014). There are many factors regulating TLR function; some of these factors include inflammation (Schroeder 2009), cytokine (Miettinen et al 2001), cellular processes such as cell migration and apoptosis (Herrera et al 2011), air pollution (Zhang and Gallo 2016), neuropsychiatric disorders (García Bueno et al 2016), drugs (Bode et al 2014a), genetic polymorphism (Tsujimoto et al 2008), physical exercise (Cavalcante et al 2018), aging (Shaw et al 2011a), and nutritional status (Vidya et al 2017). Good nutrition is required for the immune system to function properly (Mora et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, acute exercise increases pro-inflammatory cytokines, increases oxidative stress, and increases cortisol/corticosterone. When combined with physical activity in a chronic manner, this response can train the body to adapt or be more resilient to psychological and physical stress, or counteract inflammatory or other negative physiological effects of AD, leading ultimately to protection or slowing of the disease progression ( Cavalcante et al, 2017 ; Pedersen and Saltin, 2006 ).
Fig.
…”
Section: Does Chronic Physical Activity Provide Resistance or Resiliementioning
confidence: 99%